Analisis Gender âBaantaran Jujuranâ Dalam Kebudayaan Banjar - Huda, Nuril (IAIN Antasari Banjarmasin, 2014)
The people of Banjar have a unique customs their series of wedding procession. The process begins with basuluh, that is to find information on the woman who will be proposed. After basuluh, the couple should go through a series of procession such as, respectively, bedatangâthe prospective groom and his family come to meet the family of prospective bride and propose the bride, beantaran jujuranâthe groom gives dowry, a set of prayer tools, and womenâs fixtures for the bride in which both bride and groom are represented by their family, wedding ceremony, and the reception. In the process of beantaran jujuran, a representation from each family delivers marriage advice (papadahan) and rhyme for both the prospective bride and groom.This study determines to analyze the significance of beantaran jujuran and the content of papadahan and the rhyme delivered in the process of beantaran jujuran, as well as the dowry handing over. From the gender analysis point of view, beantaran jujuran in the custom of Banjar people is dominated by womenâthe bride or the brideâs mother. Moreover, the significance of the rhyme and the marriage advice in the papadahan tends to be reserved for the prospective bride, giving the impression of gender bias.